Strategi Bauran Pemasaran Terhadap Penerimaan Peserta DidikBaru Pada Lembaga Pendidikan Tinggi Di Kota Sidoarjo (Studi Kasus Di Lp3i Kota Sidoarjo) - Ihza M, Yusril; Murdaningsih, Sri Rahayu; Ariyani, Anita; D, Yuli Setyawati; Masyita, Siti; Hermawan, Sigit (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Overall, a good and effective marketing strategy in the world of education is not only about attracting new students, but also about maintaining the quality of education, building a positive image, and adapting to technological developments and the dynamics of the education market. Educational institutions need to develop inclusive and sustainable strategies to face the challenges and takeadvantage of the opportunities that exist in this modern era. The marketing strategy for educational services at LP3I Sidoarjo uses an effective marketing mix in attracting the interest of new students. Factors such as internship and work placement facilities, company relations, trusted brands, popular majors, supporting infrastructure, and strategic location are the main determinants in increasing the interest of prospective students. However, higher costs and interest in public universities are challenges that must be overcome. This type of research is qualitative with the research object being LP3I Sidoarjo. Data collection through interviews, observation,documentation and literature study. The results of marketing mix design at higher education institutions in this research show that withproper marketing mix planning it can have an effective impact in attracting the interest of new students